Toleransi Beragama Berbasis Akidah dan Ibadah di Bali: Analisis Ijtima’ Ulama Komisi Fatwa se-Indonesia VIII Nomor 02/Ijtima’ Ulama/VIII/2024 Tentang Salam Lintas Agama - Moh. Romli; Muhammad Ihyaul Fikro (Reslaj: Religion Education Social Laa Roiba Journal, 2024)
Regarding tolerance, nowadays we often hear the expressions, "tolerance is abysmal" and "Muslims fight, but non-Muslims make out." Furthermore, they do not hesitate to claim that they are "infidels, heretics and experts in hell". These expressions and claims seem to be very easy to throw at the interactions of tolerance carried out by Muslims and non-Muslims. In this problem, the root is about faith and worship. The case of religious tolerance, which is not in the realm of faith, is linked to faith, so it is easy to claim infidelity. Casuistics which in essence do not include Mahdhah worship are dragged into accusations of Mahdhah worship, the accusation is also infidelity. Muslim and Hindu religious tolerance in Bali cannot simply be linked to random beliefs and worship. Thus, this study aims to 1) emphasize the realm of belief in Islamic teachings which cannot be arbitrarily claimed as infidel in cases that are not included in the belief, 2) classify worship, that worship in Islam is divided into mahdhah and ghairu mahdhah. These two parts have different legal consequences, 3) strengthening religious tolerance in Bali which has long been established and harmonious, as well as dispelling accusations that often misuse the basic domain, 4) contributing to fatwa in religious tolerance. Because in the author's search, no MUI fatwa regarding religious tolerance was found, especially in Bali.